Primary and Secondary Lysosomes in Megakaryocytes and Platelets from Cattle with the Chediak-Higashi Syndrome - Ménard, Michèle; Meyers, Kenneth M; Prieur, David J (Thrombosis and Haemostasis, 1990)
The ultrastructure of lysosomes from megakaryocytes (MK) and platelets of cattle with the Chediak-Higashi syndrome (CHS) was characterized using acid phosphatase histochemistry with beta-glycerophosphate as substrate and cerium as a capturing agent. Acid phosphatase was localized in the trans aspect of the Golgi complex and/or granules in MK at all stages of maturation. Morphometric analysis of the diameter of each lysosome was performed on MK from CHS cattle and compared to MK from normal cattle. Lysosomes in CHS MK were neither enlarged nor different with respect to classification as secondary lysosomes, which composed 35% of the lysosomes in CHS MK. Lysosomes were demonstrated in 22% of the CHS platelet sections and appeared similar to those from normal cattle, 56% of them being classified as secondary lysosomes. Why lysosomes are not enlarged in bovine CHS MK and platelets, whereas they are enlarged in most other cell types, remains unknown.